Observation of B0s–B[bar]0s mixing and measurement of mixing frequencies using semileptonic B decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (The European physical journal. C, Particles and fields, 2013)
The $B^{0}_{s}$and B0 mixing frequencies, Δmsand Δmd, are measured using a data sample corresponding to an integrated luminosity of 1.0 fb−1 collected by the LHCb experiment in pp collisions at a centre of mass energy of 7 TeV during 2011. Around 1.8×106 candidate events are selected of the type $B^{0}_{(s)} \to D^{-}_{(s)} \mu^{+}$(+ anything), where about half are from peaking and combinatorial backgrounds. To determine the B decay times, a correction is required for the momentum carried by missing particles, which is performed using a simulation-based statistical method. Associated production of muons or mesons allows us to tag the initial-state flavour and so to resolve oscillations due to mixing. We obtain $$\begin{aligned} &\Delta m_s = \bigl( 17.93 \pm0.22\textrm{(stat)} \pm0.15 \textrm{(syst)}\bigr)~\textrm{ps}^{-1}, \\ &\Delta m_d = \bigl( 0.503 \pm0.011\textrm{(stat)} \pm0.013 \textrm{(syst)}\bigr)~\textrm{ps}^{-1}. \end{aligned}$$